PREVALENCE OF THE LEVEL OF PHYSICAL ACTIVITY AND ITS RELATIONSHIP WITH BODY MASS INDEX ADULT USERS IN THE CENTRALUBS OF PORTÃO CITY, RS (Fiep Bulletin - online, 2013)
This study aimed to determine the prevalence of physical activity level and its relationship with body mass index in adult users of the centre UBS in the city of Portão, RS. This study was characterized as observational and descriptive. Were part of the search 278 users of SUS, of both sexes, being 208 (74.8%) female and 70 (25.2%) males, aged between 21 and 59 years. Data was collected through a questionnaire with socio-demographic data, health conditions and risk factors and IPAQ 8 short version and measures of body mass index, adopting criteria set by WHO (1997). It was concluded that there is predominance in the ranking with 40.3% insufficiently active, being 112 people of the total sample and for body mass index there was predominance in excess of weight with 66.2% (184), i.e. 106 (38.1%) overweight, 72 (25.9%) obese and 6 (2.2%) severe obesity. The average BMI of the total sample was 27.7 which fits in the index of overweight, high risk to health, 55% of the samples are in the age group from 30 to 49 years, with the average age of 40.3 years. According to data obtained in this study, we can establish rates relating to the risk factors to health in the sample, i.e., diabetes (6.8%), alcoholism (22.3%), tobacco (23%), obesity grade I and II (28.1%), hypertension (33.8%), overweight (38.1%) and sedentary (40.3%). The level of physical activity prevalence, overweight and obesity was high. The results suggest the need for adoption of measures for control and prevention of obesity by the boards of health.
Keywords: physical activity level; body mass index; risk factors and public health